The role of robotic technology in minimally invasive surgery for mitral valve disease. (3rd October 2021) - Bonatti, Johannes; Kiaii, Bob; Alhan, Cem; Cerny, Stepan; Torregrossa, Gianluca; Bisleri, Gianluigi; Komlo, Caroline; Guy, T. Sloane
ABSTRACT: Introduction: Robotic mitral valve surgery has developed for more than 20 years. The main purpose of robotic assistance is to use multiwristed instruments for surgical endothoracic maneuvers on the mitral valve without opening the chest. The surgeon controls the instruments remotely from a console but is virtually immersed into the operative field. Areas covered: This review outlines indications and contraindication for the procedure. Intra- and postoperative results as available in the literature are reported. Further areas focus on the technological development, advances in surgical techniques, training methods, and learning curves. Finally we give an outlook on the potential future of this operation. Expert opinion: Robotic assistance allows for the surgically least invasive form of mitral valve operations. All variations of robotic mitral valve repair and replacement are feasible and indications have recently been broadened. Improved dexterity of instrumentation, 3D and HD vision, introduction of a robotic left atrial retractor, and adjunct technology enable most complex forms of minimally invasive mitral valve interventions through ports on the patient's right chest wall. Application of robotics results in significantly reduced surgical trauma while maintaining safety and outcome standards in mitral valve surgery.